Introduction of Mutation on Aspergillus niger by Chemical and Physical Methods for Improved Bioleaching of Bauxite - Mukherjea (Nee Bandyopadhyay), Nibedita; Banik, A.K. (Asian Journal of Chemistry, 2010)
The wild strains of Aspergillus niger isolated from soils are found to be capable of removing siliceous and iron impurities from bauxite ore in laboratory conditions. Mutation was induced in the wild strain to achieve better leaching. Chemical mutation by ethylene imine produced mutant strain A. niger AB101 which could effect a leaching of 22.7 and 25% of silica and iron, respectively, from bauxite ore. In order to improve the leaching further, mutation with X-ray was tried which could enhance the leaching appreciably to 49.8 and 56.5% for silica and iron, respectively from bauxite ore.